A Multimedia Database For Musculoskeletal Tumour Surgery - Mat Zin, Nor Azman (2001)
Management of patients with musculoskeletal tumour produced a lot of data. Besides the basic patients' data that can be stored as texts and numbers, there are also multimedia data which consists of photographic images, radiological images as well as video clips that need to be stored to improve patient care. An efficient method to manage the large amount of data is needed. A multimedia database system can be used to achieve this goal. It will facilitate clinical audit reporting, research and education. A multimedia database for musculoskeletal tumour surgery was developed using Microsoft Access~ 2000 that runs on the majority of windows-based personal computers. The database currently has records of 170 patients. The main database is 4 megabytes in size and the multimedia data occupied 5 gigabytes of storage. The present hospi tal database Lifeline® only stores the basic patients' demographic data and the Pathspeed® PACS only stores the radiological image data whereas this database can store all the above data which include the multimedia data. Compared to the traditional paper-based record system, the database offered improved legibility and centralized and structured data. It has eased the entry and coding of data, searching as well as providing easy access to the patients' multimedia data. It can automatically output basic descriptive statistics in a real-time manner that helps in clinical audit and research. The mul timedia database is also useful for education and preparation of scientific presentations.